The Impact of Covid-19 Pandemic on Audit Quality: The Perception of Indonesian Auditors - Yuniarwati -; I Cenik Ardana (International Journal of Application on Economics and Business, 2023)
The thick atmosphere of uncertainty at the macro and micro economic levels due to the Covid-19 pandemic can affect audit quality. The purpose of this study is to provide empirical evidence about the impact of the Covid-19 pandemic on audit quality from the perceptions of Indonesian auditors. The population of this research is all auditors who work in Public Accounting Firms in Indonesia. Samples were selected randomly from those who were willing to fill out a questionnaire. Dissemination of the questionnaire using google forms. The data was processed using Excel and SPSS software. Hypothesis testing using a non-parametric One Sample Wilcoxon Signed Ranks Test. The results of this study indicate that the Covid-19 pandemic has a significant effect on audit quality on all dimensions of audit quality (going concern, audit fees, auditor HR quality, audit procedures, and auditor salaries). Learning from the case of the Covid-19 pandemic, it is necessary to change the audit paradigm through increasing technological competence and digital transformation in training and audit practices going forward.